IMPLEMENTATION OF WASTE MANAGEMENT PROGRAM IN GEDAWANG KELURAHAN, BANYUMANIK DISTRICT SEMARANG CITY - Robby Firly Yassindra; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Garbage is a discussion of the most important point that is lived by the City of Semarang. In overcoming this, the Semarang City Government is promoting a solid waste management program which includes the establishment of a waste bank in every kelurahan, one of which is in Gedawang Village. In practice, every waste bank must be influenced by several factors that support or hinder the performance of the waste bank. This study aims to analyze the supporting factors and inhibiting factors that affect the implementation of the Solid Waste Management Program in Gedawang Village with reference to three aspects according to the 2016-2021 DLH RENSTRA Program Indicators in Chapter VI. The research uses qualitative methods with descriptive-narrative research design. Data obtained from observations and interviews with managers and members of the Waste Bank in Gedawang Village, Banyumanik District, Semarang City. The results of the study indicate that there is one supporting factor, namely regulation and three inhibiting factors, namely the level of waste handling services for facilities and infrastructure, and the percentage of waste volume from TPS. More inhibiting factors then result in not optimal waste management. The recommendation that can be given is to improve the habit of using waste so that they can recycle or replace it with goods that are more environmentally friendly between the Environment Service, Waste Bank, and the Community.